A novel combined biomass and solar energy conversion-based multigeneration system with hydrogen and ammonia generation. (29th April 2021) - Tukenmez, Nejat; Koc, Murat; Ozturk, Murat
Abstract: In the present study, an innovative multigeneration plant for hydrogen and ammonia generation based on solar and biomass power sources is suggested. The proposed integrated system is designed with the integration of different subsystems that enable different useful products such as power and hydrogen to be obtained. Performance evaluation of designed plant is carried out using different techniques. The energetic and exergetic analyses are applied to investigate and model the integrated plant. The plant consists of the parabolic dish collector, biomass gasifier, PEM electrolyzer and hydrogen compressor unit, ammonia reactor and ammonia storage tank unit, Rankine cycle, ORC cycle, ejector cooling unit, dryer unit and hot water production unit. The biomass gasifier unit is operated to convert biomass to synthesis gaseous, and the concentrating solar power plant is utilized to harness the free solar power. In the proposed plant, the electricity is obtained by using the gas, Rankine and ORC turbines. Additionally, the plant generates compressed hydrogen, ammonia, cooling effect and hot water with a PEM electrolyzer and compressed plant, ammonia reactor, ejector process and clean-water heater, respectively. The plant total electrical energy output is calculated as 20, 125 kW, while the plant energetic and exergetic effectiveness are 58.76% and 55.64%. Furthermore, the hydrogen and ammonia generation are found to be 0.0855 kg/s and 0.3336 kg/s. Highlights: A novel solar/biomass integrated plant for H2 and NH3 production is proposed. Comprehensive parametric work is done by varying several indicators. The power output of the designed integrated plant is 20 MW. Efficiency of 58.76% with 0.0855 kg/s hydrogen and 0.3336 kg/s ammonia is achieved.